Neuropathological abnormalities of the corpus callosum in schizophrenia: a diffusion tensor imaging study. Issue 2 (1st February 2000) - Foong, J; Maier, M; Clark, C A; Barker, G J; Miller, D H; Ron, M A
Abstract : OBJECTIVES: Diffusion tensor imaging (DTI), a technique capable of examining water diffusion in different tissues and the organisation of white matter tracts, was used to investigate the neuropathology of the corpus callosum in vivo in patients with schizophrenia. METHODS: Diffusion tensor imaging was performed in 20 schizophrenic patients and 25 healthy controls. Two complementary measures, mean diffusivity and fractional anisotropy, which are considered to be sensitive indices of axonal integrity, were obtained from regions of interest in the genu (anterior) and splenium (posterior) of the corpus callosum. RESULTS: Mean diffusivity was significantly increased and fractional anisotropy significantly reduced in the splenium but not the genu of the corpus callosum in the schizophrenic group compared with controls. There were no significant sex differences in the DTI measures for either the schizophrenic or control group. Clinical variables such as age, duration of illness, dose of antipsychotic medication, and schizophrenic symptoms did not predict the DTI changes in the schizophrenic patients. CONCLUSIONS: The presence of DTI changes in the splenium but not the genu of the corpus callosum suggests that there may be a focal disruption of commisural connectivity in schizophrenia. However, these findings do not exclude the possibility of abnormalities in other areas of the corpus callosum or other regions of white matter and further research using different methods of analysis may enable us to clarify this. Diffusion tensor imaging is a valuable tool in investigating the structure of white matter in schizophrenia.